(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study conducts a comparative analysis of gender representation and identity within thepoetry composed by Kamala das. With an emphasis on diverse gender identities, the research scrutinizesKamala das’ unique approach to depicting gender within her literary creations. Employing a comparativeframework, the study accentuates the deviations between Kamala das’ nuanced portrayals and theprevalent societal norms and literary conventions concerning gender. Kamala Das can be accomplishedthrough appreciating the things she does throughout the story. This happens as a direct consequence ofthe sexual and romantic relationship between the two parties. Her passion to poems is at risk of beingalienated by her addiction to two phases as a result of the fact that she puts herself under unnecessarystress by worrying about a variety of various characteristics of love. Even while her fixation on sensuallove throughout the first stage of the game is quite well-known, during the second stage of the game, herpath toward full adoration may set her apart from the other competitors. By juxtaposing variousexpressions of gender identity present in Kamala das’ poetry, this research unearths the poet’s intricateperspectives on the intricate interplay between gender, identity, and society. This exploration serves tofoster broader dialogues on the transformative potential of literature in reshaping and challengingestablished perceptions of gender, while shedding light on Kamala das’ innovative narrative techniques.Ultimately, this study contributes to a deeper comprehension of the role of literary art in influencing andreconstructing societal understandings of gender.